Peran Ormas Islam dalam Membina Keberagamaan Remaja - Ida Novianti (KOMUNIKA: Jurnal Dakwah dan Komunikasi, 2008)
teenage is an unique phase of life, a transition from childhood to adult. In this transition, teenager oftenbecome confuses to determine his self and future. In this confusion, teenager becomes focus of attention, from parent,family, school or Islamic social organization. There’s several reason Islamic social organization have attention to teenage, oneof it is because they have attention to religion, social, and community problems. Their role is by routine and planned religiousteaching.